A rhetorical analysis of speeches delivered by Malaysian chief executive officers according to economic climate (1998-2008) - Khor, Mi Nee (2012)
During the period of 1998-2008, Malaysia survived three major economic crisis episodes: the Asia Crisis, the dot.com crisis, and the global recession. This study was designed to discover the application of the canons of invention and organization by Malaysian CEOs during to these economic climates. A modified version of neo-Aristotelian criticism was used to analyze twentysix CEOs’ formal business speeches selected from 1998 –2008. The four CEOs were from different publicly listed companies to ensure that the findings in terms of the relationship between discourse and economic climates were due to the relationship between economic climate and rhetoric and not the nature of the company the CEO represented. The findings revealed that the Malaysian CEOs used different rhetorical strategies during thedifferent economic periods. While they showed their ethos in speeches throughout each period in similar ways, their uses of pathos, or emotional appeals, varied slightly in response to the differn of organization varied more broadly. During the first economic perithe one CEO who was studied appealed to the emotion of fear. The CEO only applied three types of logical appeals (fact, explanation, and quantification) during this time. He used the chronological and Monroe's motivated sequence arrangement patterns as well as three other types of arrangements (topical sequences, cause and effect, problem and solution) in this pessimistic economic climate. During the second economic period of 1999-2001, the economic climate was one of recovery, and the CEOs who were studied appealed to the emotion of friendship through pathos. In addition to fact, explanation, and quantification, they also used the logical evidence of definition and serial examples. Regarding the canon of organization, the CEOs only applied topical sequences, cause and effect, problem and solution arrangements. During the third economic period of 2002-2008, the CEOs stirred the emotions of kindness and pride when the economy was experiencing growth. They used a total of six types of logical evidences out of the fifteen that the researcher considered: fact, explanation and quantification,definition, serial example, and extended example. In this optimistic economic period, the CEOs added three organizational patterns to the ones used during the second economic period: chronological, Monroe's motivated sequence, and the comparative advantage pattern. In summary, this analysis indicates that the CEOs altered their arrangement patterns in ways that could be linked to the economic conditions. While their uses of ethical and emotional appeals were fairly standard, with pathos having a few changes in different periods, their modification of the types of logical evidence and arrangement patterns was moderate. The study concludes that the CEOs in Malaysia flexibly adjusted and altered the canons of invention and organization according to the rhetorical situation—in this case, the economic climate. Practically, this study can assist and guide corporate leaders to think about and advance their business rhetorical skills in practical ways, particularly in the context of the Malaysian economy.